The American short story handbook - Nagel, James (Chichester, West Sussex, [England] John Wiley & Sons, Ltd., 2015)
"This is a concise yet comprehensive treatment of the American short story that includes an historical overview of the topic as well as discussion of notable American authors and individual stories, from Benjamin Franklin's "The Speech of Miss Polly Baker" in 1747 to "The Joy Luck Club". Includes a selection of writers chosen not only for their contributions of individual stories but for bodies of work that advanced the boundaries of short fiction, including Washington Irving, Sarah Orne Jewett, Stephen Crane, Jamaica Kincaid, and Tim O'Brien Addresses the ways in which American oral storytelling and other narrative traditions were integral to the formation and flourishing of the short story genre Written in accessible and engaging prose for students at all levels by a renowned literary scholar to illuminate an important genre that has received short shrift in scholarly literature of the last century Includes a glossary defining the most common terms used in literary history and in critical discussions of fiction, and a bibliography of works for further study."--Provided by publisher.
"The Handbook of the American Short Story is a concise yet comprehensive treatment of the topic that is designed to illuminate an important literary genre that has been given short scholarly shrift over the last century."-- Provided by publisher.
Part IV: Great American short stories -- Benjamin Franklin, "The Speech of Polly Baker" -- Ruri Colla, "The Story of the Captain's Wife and an Aged Woman" -- Washington Irving, "Rip Van Winkle" -- Nathaniel Hawthorne, "Young Goodman Brown" -- Edgar Allan Poe, "The Cask of Amontillado" -- Herman Melville, "Bartleby, the Scrivener" -- Frances Ellen Watkins Harper, "The Two Offers" -- Hamlin Garland, "Under the Lion's Paw" -- Charlotte Perkins Gilman, "The Yellow Wallpaper" -- Henry James, "The Real Thing" -- Kate Chopin, "Desiree's Baby" -- Ambrose Bierce, "An Occurence at Owl Creek Bridge" -- Stephen Crane, "The Blue Hotel" -- Frank Norris, "A Deal in Wheat" -- Edith Wharton, "The Other Two" -- Willa Cather, "A Wagner Matinee" -- Jack London, "To Build a Fire" -- Jean Toomer, "Blood-Burning Moon" -- F. Scott Fitzgerald, "Babylon Revisited" -- Ernest Hemingway, "Indian Camp" -- John Steinback, "The Chrysanthemums" -- Eudora Welty, "Petrified Man" -- William Faulkner, "Barn Burning" -- Flannery O'Connor, "The River" -- Tillie Olsen, "Help Her to Believe" ["I Stand Here Ironing"] -- Raymond Carver, "Cathedral" -- Louise Erdrich, "The Red Convertible" -- Susan Minot, "Hiding" -- Amy Tan, "The Joy Luck Club" -- Tim O'Brien, "Sweetheart of the Song Tra Bong" -- Jamaica Kincaid, "Columbus in Chains" -- Judith Cofer, "Nada".
Includes bibliographical references (pages [303]-305) and index.
Keywords: Short stories, American -- History and criticism -- Handbooks, manuals, etc